1976
DOI: 10.1085/jgp.67.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the red blood cell membrane during the active transport of C++.

Abstract: The phosphorylation of red blood cell membrane fragments (RBCMF) during Ca ++ transport was investigated. When red cell membrane fragments are incubated with [y-a2P]ATP under the experimental condition which minimizes the phosphorylation of Na+-K+-ATPase, RBCMF are labeled in the presence of Mg ++ without Ca ++. When Ca ++ is added, the labeling decreases due to dephosphorylation of RBCMF. The initial reaction of phosphorylation is reversed in the presence of excess ADP. The treatment of RBCMF with n-ethylmale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This agreed with the finding that a sulfhydryl inhibitor structurally similar to NEM, diamide, locks Na ϩ / Ca ϩϩ exchange in dog erythrocytes in an "on" conformation (Parker, 1986). NEM also blocks dephosphorylation of Ca ϩϩ -ATPase, indicating that the pump is unable to turn off (Cha and Lee, 1976). Therefore, when AsH 3 is present, NEM offers its hemolytic protection to erythrocytes by facilitating Ca ϩϩ efflux.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This agreed with the finding that a sulfhydryl inhibitor structurally similar to NEM, diamide, locks Na ϩ / Ca ϩϩ exchange in dog erythrocytes in an "on" conformation (Parker, 1986). NEM also blocks dephosphorylation of Ca ϩϩ -ATPase, indicating that the pump is unable to turn off (Cha and Lee, 1976). Therefore, when AsH 3 is present, NEM offers its hemolytic protection to erythrocytes by facilitating Ca ϩϩ efflux.…”
Section: Discussionsupporting
confidence: 87%
“…The effect of NEM on Mg ϩϩ transport seems to be inhibitory although there is very limited data to support this finding. There is some evidence that NEM inhibits Ca ϩϩ ,Mg ϩϩ -ATPase (Cameron and Smariga, 1981;Cha and Lee, 1976) supporting the finding that NEM decreases intracellular Mg ϩϩ concentrations. NEM was ineffective in preventing AsH 3 -induced increase in intracellular Clconcentration.…”
Section: Discussionmentioning
confidence: 81%
“…It has been observed that both calcium and higher levels of magnesium can induce the phosphorylation of erythrocyte membrane proteins by ATP (Knauf, Proverbio & Hoffman, 1974;Rega& Garrahan, 1975;Cha & Lee, 1976) and both types of phosphate bonds are abolished by hydroxylamine. It has also been noted that the phosphoprotein formed in the presence of calcium was dephosphorylated by magnesium (Rega & Garrahan, 1975) while the phosphoprotein formed in the presence of magnesium was dephosphorylated by calcium (Cha & Lee, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been noted that the phosphoprotein formed in the presence of calcium was dephosphorylated by magnesium (Rega & Garrahan, 1975) while the phosphoprotein formed in the presence of magnesium was dephosphorylated by calcium (Cha & Lee, 1976). One might speculate that the transport of calcium from erythrocyte ghosts may proceed by two mechanisms.…”
Section: Discussionmentioning
confidence: 99%